2017
DOI: 10.18697/ajfand.80.16345
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ views and use of labels on food items sold in Bulawayo urban province, Zimbabwe

Abstract: Food labels are a medium by which consumers acquire knowledge about packaged foods they are considering to purchase. The label makes the first impression about a product and has a great effect on the purchasing decision for consumers. In recent years, literate consumers have become interested in nutritional issues. Lifestyle, age, dietary and safety concerns have been the contributing factors to nutritional awareness by consumers. Nutritional labels can generally have a positive impact on food consumption and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…However, Moyo [4] pointed out how urban agriculture's potential was constrained by a complex of factors that include invasion due to the growth of built-up areas, land tenure insecurity, erratic water access, small plot sizes, inadequate capital for optimizing plot productivity, and ambivalent application of urban land-use laws. A similar study by [6] confirmed that urban agriculture contributes significantly to food security in Old Pumula, Bulawayo, but also revealed that urban farmers are faced with severe land shortages and are restricted by by-laws from practicing urban agriculture. Evidently, urban agriculture is valuable enough that trends in production need to be analyzed as cities grow.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…However, Moyo [4] pointed out how urban agriculture's potential was constrained by a complex of factors that include invasion due to the growth of built-up areas, land tenure insecurity, erratic water access, small plot sizes, inadequate capital for optimizing plot productivity, and ambivalent application of urban land-use laws. A similar study by [6] confirmed that urban agriculture contributes significantly to food security in Old Pumula, Bulawayo, but also revealed that urban farmers are faced with severe land shortages and are restricted by by-laws from practicing urban agriculture. Evidently, urban agriculture is valuable enough that trends in production need to be analyzed as cities grow.…”
Section: Introductionmentioning
confidence: 69%
“…Although previous studies such as Moyo et al. [11], Mbiba [5], and Ncube and Ncube [6] stressed the value of urban agriculture in sustaining the lives of citizens, especially the low-income strata, studies that relate the growth of cities to food security in Zimbabwe are scarce. Unfortunately, as most of the planted area is not registered with the municipalities for the purposes of formal agriculture, it is hard to quantify the contribution of urban farming to livelihood and food security in response to city expansion trends.…”
Section: Introductionmentioning
confidence: 99%
“…Some other articles reported that difficulty in understanding was a substantial barrier to consumer use of nutrition labels. In Zimbabwe, one article reported that mistrust of nutrition labels (44.0%) was the principal barrier to the use of nutrition labels (Ncube et al, 2017). All the research articles from Lesotho and Malawi did not report on barriers to consumer use of nutrition labels (Kasapila & Shawa, 2011; Mahgoub et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…In South Africa, those who speak English, the educated, and the young were the categories of consumers identified as likely to use nutrition labels (van der Merwe et al, 2013). Furthermore, a study in Zimbabwe identified only females as consumers likely to use nutrition labels (Ncube et al, 2017). Finally, in Nigeria, Malawi, and Ethiopia, the educated, female, and high-income earners were the categories of consumers reported as likely to use nutrition labels (Falola, 2014; Feyisa et al, 2021; Kasapila & Shawa, 2011).…”
Section: Resultsmentioning
confidence: 99%